REDESIGN, SYNTHESIS, AND ENZYMATIC HYDROLYSIS PROFILE OF TRIHYBRIDE COMPOUND OF NONSTEROIDAL ANTI-INFLAMMATORY DRUG-CYSTEIN-NITRATE AS NOVEL ANTI-INFLAMMATORY PRODRUG - Harmastuti, Nuraini
Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) are a class of drugs commonly used for symptomatic treatment of various diseases accompanied by symptoms of inflammation through inhibition of prostaglandin biosynthesis. However due to protective effects of prostaglandin in gastrointestinal tract, iritation and ulcers of gastrointestinal tract followed by a disruption of blood flow to the ulcer area are typical side effect of this class of drugs. Meanwhile dihydrids of free thiol-nitric oxide (NO) donors are able to release NO slowly as a vasodilator and hence does not cause a drastic decrease in blood pressure as well as free of nitrate tolerance. Applying this fact, a strategy to reduce the adverse side effects of NSAIDs on the gastrointestinal tract is developing the concept of trihybride of NO donor-cysteine / homocysteine-NSAIDs which is expected to improve blood flow to the ulcer area and hence can reduce typical side effects of conventional NSAIDs. The aims of this research were to obtain a thrihybride of N-Nitrate-cysteine-S-NSAID with high purity and in sufficient quantity as well as its enzymatic hydrolysis profile in releasing free NSAID under in vitro physiologic condition. To achieve these goals, the research was divided into three main stages. The first stage was the in silico study of four thrihybride design compounds potentially able to release NSAIDs including N-nitratopivaloyl-cystein-S-naproxene, Nnitratopivaloyl-homocysteine-S-naproxene, N-nitratopivaloyl-cystein-Sdiclofenac, and N-nitratopivaloyl-homocysteine-S-diclofenac. The study was conducted using various computer application programs including PreAdMet, MarvinSketch, Meteor and AutoDock Tools. The study was initiated by application of Lipinski`s rule to estimate the oral absorption possibility of those compounds, followed by predictions of absorption parameters using the PreADMET program. The biotransformation pathways of those compounds were predicted by the Meteor program, while their affinities on Acyl Protein Thioesterase1 (APT1) as the relevant hydrolyzing enzyme were studied by means of docking method using the Autodock Tools program. Based on in silico study results, a suitable thrihydride compound to be synthesized could be selected. The second stage was the synthesis of the selected / target iv trihydride compounds consisting of nitration, ester hydrolysis, and N- and Sacylation reactions. The third stage was the enzymatic hydrolysis test of the selected/target trihibride compound under in vitro physiologic condition. The application of Lipinski's rule to the four compounds revealed that all compounds violated the rule. However, based on human intestinal absorption (% HIA), all compounds were predicted to be high (?90%), while their permeability rates were predicted to be low in the case of N-nitratopivaloil-cysteine-Snaproxene and N-nitratopivaloil-homocysteine-S-naproxene (?4 nm / sec.) and medium in the case of N-nitratopivaloil-cysteine-S-diclofenac and Nnitratopivaloil-homocysteine-S-diclofenac (4 - 70 nm / sec.). The prediction results of biotransformation by Meteor showed that each trihibride compound has a hydrolysis path profile with the same likelihood rating. Of the three types of ester bonds, hydrolysis of nitrate ester was predicted as the first metabolic step followed by hydrolysis of carboxylic esters as the second hydrolysis pathway, categorized as probable, which is the highest level of possibility. The last step was hydrolysis of thioester at plausible level. The results of molecular docking studies showed that all compounds would have similar affinities on APT1 proteins with patterns equivalent to the original ligands, predicted in terms of Gibbs free binding energy (?G), contributing amino acid residues, and the number of hydrogen bonds taking part in the interactions, mainly involved residues of Ser119, Leu30, and Gln120. Based on these results, the trihibride N-nitratecysteine-S-diclofenac was selected as a novel candidate of nonsteroidal antiinflammatory prodrug to be synthesized. The target compound N-nitratopivaloil-cysteine-S-diclofenac trihibride was obtained in the following steps: synthesis of nitratopivaloic acid methylester (3- nitrato-2,2-dimethylpropanoic acid methylester) (compound 01), nitratopivaloic acid (3-nitrato-2,2-dimethylpropanoic acid) (compound 02), nitratopivaloyl chloride (compound 03), N-nitratopivaloyl-L-cysteine ethylester (compound 04), and target compound N-nitratopivaloyl-cysteine-S-diclofenac (compound 05). The target compound was successfully obtained with crude yield of 64% and following preparative HPLC purification, with the recovery and purity of 75% and 98.6%, respectively. The 1 H- and 13 C-NMR spectrums of the target compound are in line with the structure of N-nitratopivaloil-cysteine-S-diclofenac. Upon enzymatic treatment with porcine hepatic esterase under in vitro physiologic condition, the target compound was hydrolyzed to release diclofenac as free NSAID with the rate of 24.4% after 24 hours incubation time, which is greater than previous result of 16% in the case of N-nitratopivaloyl-cysteine-Snaproxen thrihybride under similar experiment condition. This result confirms that the reduction of steric hindrance on one side of carbonyl thioester of Nnitratopivaloyl-cysteine-S-naproxen through removal of ?-methyl group of NSAID can enhance increase the release of NSAID from thioester bonds.